Ответы и объяснения

2013-11-24T17:59:14+00:00
1.
 x^{3} - 4x^{2} -9x+36=0
( x^{3} - 4 x^{2}) - (9x-36)=0
 x^{2} (x-4)-9(x-4)=0
( x^{2} -9)(x-4)=0
 x^{2} =9   или   x-4=0
x1,2= 3 и -3.              x=4

Ответ: -3,3,4

2.  ( x^{2} -7)^{2} -4( x^{2} -7)-45=0
заменим  x^{2} -7 = t
 t^{2}-4t-45=0
Д=16+180=196
t1=4+14/2=9
t2=4-14/2=-5
подставляем t в выраженное выражение (x^2-7=t)
t1
x^2-7=9
x^2=16
x1=4
x2=-4

t2
x^2-7=-5
x^2=2
x1= \sqrt{2}
x2=- \sqrt{2}

3.
 x^{4} -13 x^{2} +36=0
 x^{2} =y
 y^{2} -13y+36=0
Д=(-13)^2-4*36=196-144=25
y1=13-5/2=-4
y2=13+5/2=9
подставляем у в выражение  x^{2} = y
y1
 x^{2} = 4
x1=2
x2=-2
y2
 x^{2} =9
x1=3
x2=-3